Strategies to improve the classroom space during english teaching-learning on first-year high school students at the bilingue Americano high school. - Tomala Guale, Genesis Elizabeth (2023)
The purpose of this case study is to analyze the incorrect positioning of the classroom and the reasons why it is not a good way to start the class. In addition, to implement strategies to help position the classroom to make the teaching environment more comfortable. Upon completion of the classroom observation, the students' classroom is very cramped for the number of students it has with a total of 33 students and a very limited classroom space, where it is very difficult for both the student and the teacher to move freely around the classroom. In addition, this can cause distractions and can be detrimental to the academic record of the students, something which can look very bad for the teacher and the Educational Unit. The Bilingue Americano High School classrooms do not have large classrooms for the number of students it handles, so it is essential to correct this problem. The present investigation proposes a very useful solution to correct the problem of the space in the classroom, as well as the implementation of strategies that help all the people who make up the Educational Unit, especially the students of the English class and the teacher in charge, will benefit from it.